EVALUATION OF STUDENT ABILITY IN DRAWING CONCEPT MAPS: A STUDY OF CONCEPT MAP STRUCTURE AND QUALITY - Sumiati Side; Vika Puji Cahyani (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
Concept maps are an effective tool in the learning process, enabling students to organise and structure information into a unified whole. Although there has been much research on concept maps as a learning tool, there is still limited research specifically analysing the structural patterns of concept maps and relating them to students‘ conceptual understanding or abilities. This study aims to analyse students’ abilities in constructing concept maps. This study is a quantitative descriptive study. The sample of this study were 16 students who took the basic science education course. The sample was selected using purposive sampling, namely students who had received basic chemistry material. The concept maps that had been made were then analysed based on the structural pattern used (hierarchical, network, linear, mixed) using an assessment rubric. Quantitative descriptive analysis was used to see the distribution of the pattern of students' concept maps in the form of averages, frequencies, percentages and graphic visualisations for each aspect measured in the concept maps. Based on the results of data analysis in this study, it can be concluded that most students use a hierarchical pattern (38%), followed by a network pattern (31%), a mixed pattern (25%), and a linear pattern (6%). The majority of students (62.5%) had an understanding in the very good category, 6.25% in the good category, and 12.5% in the lacking category. No students were in the very lacking category.